Objectives versus realities: Spatial, temporal, financial and social deficiencies in Australia's public revegetation investment model. (30th December 2019) - Collard, Stuart J.; O'Connor, Patrick J.; Prowse, Thomas A. A.; Gregg, Daniel; Bond, Anthelia J.
Summary: Past and continuing fragmentation and modification of ecosystems, as well as other threatening processes, cause ongoing biodiversity losses and species extinctions in Australia. At the same time as biodiversity declines, government funding for conservation and restoration is diminishing, leading to reduced action and greater reliance on private investment and community groups. In order to maintain and restore biodiverse ecosystems and the essential services they provide, both conservation of existing vegetation and habitat reconstruction are required. In this paper, we summarise the available data on planting area and cost from the Australian Government's 20 Million Trees programme (2014–2020), the largest recent national‐scale revegetation incentives programme in Australia. We find that the current spatial scale of effort and investment in habitat reconstruction is insufficient to match the scale required to meet national conservation objectives. Furthermore, the funding rate (/ha) and contracting arrangements are inadequate for the establishment of high‐quality self‐sustaining vegetation needed for the recovery of Australia's threatened species and ecological communities. We estimate that the minimum amount of funding required for habitat reconstruction is at least five times higher than is provided for current national flagship programmes such as 20 Million Trees. We provide recommendations, designed to assist future habitat reconstruction programmes achieve their long‐term biodiversity objectives.